Proposed new interior design for CT - One Forze Café at No 122 Jalan Sultan Abdul Jalil,Greentown 30450 Ipoh Perak Darul Ridzuan / Aisyah Tul Azma Zakria - Zakria, Aisyah Tul Azma (Faculty of Architecture, Planning and Surveying, 2010)
This Diploma level Interior Design final project is towards student understanding about the interior design project’s whole aspect that had been studied from the basic level until the design proposal presentation. The selected final project is a Proposed new interior design for ct-one forze cafe at no 122 Jalan Sultan Abdul Jalil, Greentown 30450 Ipoh Perak Darul Ridzuan.That is the theme restaurant that highlight the concept of military lifestyle.the concept and image is apply to both interior and exterior. With the outcome of the restaurant, it could uphold the forces as a fighter and help existing efforts in the appreciation recognition, and public awareness to the sacrification of military and their community.There were several researches done to succeed this restaurant project, amongst the, are site analysis, building analysis, interview, observation and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve of the problem that appear.